Anaerobic digestion of sewage sludge for biogas & biohydrogen production: State-of-the-art trends and prospects. (1st December 2022) - Khawer, Muhammad Usmaan Bin; Naqvi, Salman Raza; Ali, Imtiaz; Arshad, Muazzam; Juchelková, Dagmar; Anjum, Muhammad Waqas; Naqvi, Muhammad
Highlights: A critical review on anaerobic digestion of sewage sludge is presented. Technological limitations associated with each strategy have been detailed. Networking of stakeholder and commercialization aspects have been summarized. Abstract: Advancement in the anaerobic digestion of sewage sludge for biogas production is constantly required for effective commercialization. There is great interest in exploring the scientometric and technical assessment in biogas production using sewage sludge from various sources in the anaerobic digestion process. Therefore, this work provides a bibliometric and technical study of anaerobic digestion for biogas production from sewage sludge in the last ten years, based on Web of Science data. The vital parameters of the bibliometric study are authors, countries, and institutional collaboration along with the authors' keywords. In terms of technical assessment, challenges are highlighted with critical analysis of previous work performed both on a laboratory scale and on a pilot scale. The study recommends key considerations and new combination techniques to enhance biohydrogen production with optimized process conditions which will provide vital economic impact for technological adaptation and commercialization.